2010
DOI: 10.1111/j.1476-5381.2010.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide oligomerization domain 1 is a dominant pathway for NOS2 induction in vascular smooth muscle cells: comparison with Toll‐like receptor 4 responses in macrophages

Abstract: Background and purpose:Gram-negative bacteria contain ligands for Toll-like receptor (TLR) 4 and nucleotide oligomerization domain (NOD) 1 receptors. Lipopolysaccharide (LPS) activates TLR4, while peptidoglycan products activate NOD1. Activation of NOD1 by the specific agonist FK565 results in a profound vascular dysfunction and experimental shock in vivo.Experimental approach:Here, we have analysed a number of pharmacological inhibitors to characterize the role of key signalling pathways in the induction of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…No information is currently available regarding NLRs and RLRs in HASMCs. However, vascular SMCs have been reported to express NOD1 and respond to the NOD1 agonist FK565, while being unaffected by NOD2 stimulation [42], [43]. The present study complements and extends previous reports on innate immune receptors in HASMCs by showing mRNA expression for TLR2, TLR3, TLR4, TLR7, NOD1, NOD2, RIG-I, MDA-5 and LGP-2.…”
Section: Discussionsupporting
confidence: 88%
“…No information is currently available regarding NLRs and RLRs in HASMCs. However, vascular SMCs have been reported to express NOD1 and respond to the NOD1 agonist FK565, while being unaffected by NOD2 stimulation [42], [43]. The present study complements and extends previous reports on innate immune receptors in HASMCs by showing mRNA expression for TLR2, TLR3, TLR4, TLR7, NOD1, NOD2, RIG-I, MDA-5 and LGP-2.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the complete loss of this receptor significantly decreased the size of atherosclerotic lesions, providing evidence of a solid relationship between NOD1 and atherosclerosis. Previously, only limited studies have shown the effect of NOD1 in the cardiovascular field (25,26) or the involvement of NOD1 in vascular inflammation induced by C. pneumoniae (12). No prior study, however, has directly proven the association between NOD1 and atherosclerosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…24 hours later, cell viability was evaluated by the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay30 and culture medium was frozen until further analysis.…”
Section: Methodsmentioning
confidence: 99%